2004
DOI: 10.1152/japplphysiol.00977.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of five consecutive nocturnal hypoxic exposures on the cerebrovascular responses to acute hypoxia and hypercapnia in humans

Abstract: The effects of discontinuous hypoxia on cerebrovascular regulation in humans are unknown. We hypothesized that five nocturnal hypoxic exposures (8 h/day) at a simulated altitude of 4,300 m (inspired O2 fraction = approximately 13.8%) would elicit cerebrovascular responses that are similar to those that have been reported during chronic altitude exposures. Twelve male subjects (26.6 +/- 4.1 yr, mean +/- SD) volunteered for this study. The technique of end-tidal forcing was used to examine cerebral blood flow (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
(65 reference statements)
0
18
1
Order By: Relevance
“…Induction of VEacc has been reported previously during repeated daily exposures to HH or NH treatment (17,18,20,22). Acquisition and retention of VEacc resulting from the repeated HH treatment appears to be an important response associated with reduced AMS symptoms and improved TT performance during subsequent exposure to 4,300 m (2-4).…”
Section: Discussionmentioning
confidence: 59%
“…Induction of VEacc has been reported previously during repeated daily exposures to HH or NH treatment (17,18,20,22). Acquisition and retention of VEacc resulting from the repeated HH treatment appears to be an important response associated with reduced AMS symptoms and improved TT performance during subsequent exposure to 4,300 m (2-4).…”
Section: Discussionmentioning
confidence: 59%
“…This would result in relatively larger pH changes per mmHg increase in the arterial partial pressure of CO 2 during the hypercapnia sensitivity test. Since _ V E during eupnoea was similar before and after IH, this could explain the differences in the MCA V mean response to CO 2 reported by Kolb et al (2004).…”
Section: Effect Of Ih On Cerebrovascular Regulationmentioning
confidence: 79%
“…Others have shown IH to increase the cerebral sensitivity to hypercapnia. For example, Kolb et al (2004) found the cerebral sensitivity to hypercapnia was increased following five nights of eucapnic hypoxia, which can be attributed to persistent hyperventilation-induced decreases in HCO 3 -concentration in cerebrospinal fluid . This would result in relatively larger pH changes per mmHg increase in the arterial partial pressure of CO 2 during the hypercapnia sensitivity test.…”
Section: Effect Of Ih On Cerebrovascular Regulationmentioning
confidence: 99%
“…The resonator has advanced automatching and autotuning capabilities that correct for any slight animal movements. The EPR spectrum was acquired with a scan time of 30 s, and usually 10 scans were obtained and averaged to produce a signal-to-noise ratio of at least 5 (but typically [10][11][12][13][14][15][16][17][18][19][20], which allowed accurate fitting. The peak-to-peak line width of the spectrum was obtained via computer line-fitting, and converted to pO 2 values according to a calibration curve for the oximetry probe LiPc used in the study (see the following paragraph).…”
Section: Measurement Of Cerebral Po 2 By Epr Oximetry With Particulatmentioning
confidence: 99%
“…6 Although an adequate cerebral oxygen level is critical to neuron survival, monitoring oxygen levels in this tissue, in vivo and in real time, remains a technical challenge, especially in deeper tissue or for repetitive measurements. Several techniques can be used for oxygen level measurement including Clark-type electrodes 7 and fluorescence quenching (Oxylite) 8,9 for tissue oxygenation, phosphorescence quenching 10 and near-infrared spectroscopy 11 for blood oxygenation, 19 F MRI 12 and EPR oximetry with a particulate probes. Among these methods, EPR oximetry with particulate probes has several advantages, especially for the repetitive and highly accurate measurement of localized interstitial (or tissue) pO 2 .…”
Section: Introductionmentioning
confidence: 99%